The Role of Sustainable Performance as a Mediating Variable in the Relationship Between Sustainable Leadership and Sustainable Development: A Field Study in Iraqi Public Universities (Entrepreneurship Journal for Finance and Business, 2025)
The higher education sector is considered one of the important sectors and is referred to as the vital artery due to its great importance in providing the labor market and state institutions with expertise, skills and human energies. This sector's contribution to the development process by keeping pace with modern technology and sciences and its possession of enormous human competencies, expertise and potential has made this sector a major focus of interest for other sectors. The main purpose of the study is how to maintain the quality of performance and sustainability of quality through sustainable development. A random sample of workers in the higher education sector was taken and the questionnaire was the main tool for data collection, where (235) questionnaires were distributed, of which (192) were valid for use. The (SPSS) and (AMOS) Structural Equation Model (SEM) version (25) were used to analyze the data and results. There is a significant positive statistical relationship between transactional leadership and sustainable development. In addition, there was a significant impact and role of the mediating variable (performance quality) on the relationship between the independent variable (transactional leadership) and the dependent variable (sustainable development (.